2019
DOI: 10.5539/jas.v11n2p251
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-Induced Defense Response in Soybean Plants Challenged by Bemisia tabaci

Abstract: The whitefly, Bemisia tabaci Biotype B (Hemiptera: Aleyrodidae), is considered one of the world’s major agricultural pest groups, attacking a wide range of crop hosts and causing considerable crop loss. Understanding the interactions between whiteflies and host plants promotes the development of novel strategies for controlling whiteflies. This study aimed to evaluate the biochemical alterations caused by induced resistance in soybean plants, challenged by B. tabaci. The experiment was performed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Shifts in the activity patterns of defensive enzymes in response to herbivory have been previously reported in soybean. Locateli et al ( 2019 ) found higher activity of PAL in soybean plants 96 h after treatment with Bemisia tabaci , but at 168 h the PAL activity was lower than that of untreated controls. Speculatively, it may be possible that herbivore-derived effectors change the initial plant response over time.…”
Section: Discussionmentioning
confidence: 97%
“…Shifts in the activity patterns of defensive enzymes in response to herbivory have been previously reported in soybean. Locateli et al ( 2019 ) found higher activity of PAL in soybean plants 96 h after treatment with Bemisia tabaci , but at 168 h the PAL activity was lower than that of untreated controls. Speculatively, it may be possible that herbivore-derived effectors change the initial plant response over time.…”
Section: Discussionmentioning
confidence: 97%
“…According to Locateli et al. (2019), the latter could be related to a double stimulus: that of the natural defense of the fruit and that induced by Ch on the production of phenols.…”
Section: Resultsmentioning
confidence: 99%
“…Their results coincide with the results obtained in the present study because phenolic content slightly increased at day 6 when the anthracnose symptoms intensified; and also, fruit coated with the different molecular weights Ch had lower anthracnose development and higher phenolic compounds. According to Locateli et al (2019), the latter could be related to a double stimulus: that of the natural defense of the fruit and that induced by Ch on the production of phenols.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Both of inducers; SA (C7H6O3; MW = 138.12) and SMS (Na2SiO3.9H2o; MW = 284.20) were produced by Oxford Lab Chem. Mumbai, India and applied at 2 mM concentration which are considered optimal for the normal growth of bean and widely used in several studies (Hodson and Evans, 1995;Gong et al, 2005;Gunes et al, 2007;Shen et al, 2009;Locateli et al, 2019). For each variety, seven treatments were applied as described in Table (1) with three replicates for each treatment.…”
Section: Methodsmentioning
confidence: 99%